Ideas of Multipolarity in the Conceptual Frame of the Soviet Diplomacy during the Final Phases of the Great Patriotic war (1943–1945) - I. E. Magadeev (Vestnik MGIMO-Universiteta)
This article endeavors to delineate the conceptual landscape occupied by the notions of prospective multipolarity within the strategic discourse of Soviet diplomacy during the latter phases of the Great Patriotic War. Particular emphasis is placed on the intellectual contributions of two prominent Soviet diplomats, M.M. Litvinov and I.M. Maisky. The author substantiates these insights by drawing upon both published and archival source materials, including the diaries and records maintained by officials within the Soviet Foreign Office, as well as documents emanating from the "Litvinov commission."While the diplomatic theories formulated by Litvinov and Maisky during the years 1943–1945 have been subject to analysis by Russian and international scholars, the majority of extant scholarship has traditionally focused on the content and nuances of their perspectives on specific international "questions." Departing from this convention, this article adopts a methodological approach that seeks to explore the underlying conceptual foundations upon which the ideas of Litvinov and Maisky were constructed. Additionally, the essay introduces a novel dimension by surveying the viewpoints of other Soviet diplomats (S.A. Lozovskii, B.E. Shtein, Ia.Z. Surits, E.V. Tarle), who have garnered relatively less scholarly attention.Of paramount interest is the manner in which Litvinov and Maisky envisaged the post-World War II international landscape, albeit without explicitly employing the term "multipolarity." The article addresses critical questions, such as their perception of the global scenario following WWII, their consideration of the inevitability of Soviet-American bipolarity, and the factors and circumstances that influenced their conceptualizations. The contemporary resurgence of discussions surrounding the trajectory of multipolarity in the twenty-first century underscores the pertinence of this historical inquiry.The article's key conclusion posits that the conceptual framework embraced by Soviet diplomats during 1943–1945 was not centered on notions of bipolarity or an imminent Cold War. While acknowledging the potential escalation of tensions between the USSR and Western nations led by the USA and Great Britain, they favored collaboration among the principal powers of the antiHitlerite coalition, grounded in an implicit understanding of their respective "spheres of influence." Although Soviet Foreign Office officials did not discount the possibility of the formation of a united Anglo-American front against the USSR, they believed that Soviet diplomacy should actively work to prevent such an outcome by capitalizing on the fissures between Washington and London.